N6-Methyladenosine and Viral Infection - Dang, Wei; Xie, Yan; Cao, Pengfei; Xin, Shuyu; Wang, Jia; Li, Shen; Li, Yanling; Lu, Jianhong (Frontiers in Microbiology, 2019)
N6-methyladenosine (m6A), as a dynamic posttranscriptional RNA modification, recently gave rise to the field of viral epitranscriptomics. Multiple modified viral RNAs have been observed. A virus can also affect host gene expression via m6A. However, the mechanism of m6A regulation in viral infection and host immune has not been thoroughly elucidated to date. With the development of sequencing-based biotechnologies, transcriptome-wide mapping of m6A in viruses has been achieved, laying the foundation for expanding its functions and corresponding mechanisms. In this report, we summarize the positive and negative effects of m6A in distinct viral infection. Given the increasingly important roles of m6A in diverse viruses, m6A represents a novel potential target for antiviral therapy.